Syn-BN-heteroacene cored conjugated oligomers with finely tuned blue-violet luminescent properties. Issue 34 (18th August 2017) - Zhang, Wanzheng; Fu, Yubin; Qiang, Peirong; Hunger, Jens; Bi, Shuai; Zhang, Wenbei; Zhang, Fan
Abstract : Starting from dibrominated syn -BN-heteroacenes, a series of BN-containing conjugated oligomers with blue-violet luminescence was synthesized. Abstract : Initiated by the effective dibromination of syn -BN-heteroacenes, a series of BN-containing conjugated oligomers was successfully synthesized upon transition-metal-catalyzed cross coupling. Their electronic structures can be finely tailored through varying the fused backbone or terminal substituents, endowing them with tunable luminescent properties within blue-violet regions.